COMMUNICATING CONFIDENCE: SUSPENDED SENTENCES AS COMMUNICATIVE PUNISHMENT - Plesnicar, Mojca; Tripkovic, Milena (Pravni zapisi, 2024)
The article identifies a distinctive model of suspended sentences that exists in contemporary Serbia and Slovenia. By employing Antony Duff’s notion of ‘communicative punishment’, the article suggests that suspended sentences are a robust and comprehensive penal instrument which promotes an inclusive, dialogic, and non-stigmatizing approach to criminal offenders. To demonstrate this, the article contrasts Duff’s theory with three key domains of suspended sentences in the two countries: (a) philosophical and theoretical commitments, (b) substantive and procedural law and (c) execution of sanctions. The article concludes by emphasizing the pronounced capacity of these sentences to communicate confidence and trust of the state that the convicted person will not reoffend – despite a non-custodial sanction. Finally, the article proposes modest legal modifications which pertain to the court’s ability to determine relevant facts and communicate better with the offender.
Keywords: Suspended sentence; Communicative punishment; Probation; Crime; Punishment; Sentencing; Criminal law; Antony Duff; Serbia; Slovenia